Evaluation of a self-monitoring protocol for assessing soot and polycyclic aromatic hydrocarbon exposure among chimney sweeps - Klang, Therese; Molnár, Peter; Lindh, Christian; Storsjö, Tobias; Tinnerberg, Håkan (Frontiers in Epidemiology, 2024)
Traditional methods to measure chemical exposure have challenges in terms of obtaining sufficient amount of data and therefore improved methods for better assessment of occupational exposure are needed. One possible approach to mitigate these challenges is to use self-monitoring methods such as sensors, diaries or biomarkers to study the exposure. In the present study a self-monitored method to measure soot exposure was evaluated, which included real-time air monitoring, a work diary and collection of urine samples. To validate the method, exposure measurements during the workday and diary entries have been compared with velocities calculated from GPS-tracking and expected patterns for polycyclic aromatic hydrocarbon (PAH)-metabolites in urine. The method was applied on chimney sweeps, which is an occupational group with high risks for many severe health outcomes and where effective control measures to reduce the exposure is needed. In the study, 20 chimney sweeps followed a self-monitoring protocol for eight consecutive workdays. Personal exposure to soot was measured as black carbon (BC) with micro-aethalometers. A diary was used to record work tasks performed, and urine samples were collected and analysed for metabolites of PAH. From the expected 160 full day measurements, 146 (91%) BC measurements and 149 (93%) diaries were collected. For the expected 320 urine samples 304 (95%) were collected. Task noted in the diaries overlapped with information from the GPS-tracking of the chimney sweeps during 96% of the measurement time. The PAH-metabolites in urine increased during the work week. Factors believed to have positively influenced the sample collection and task documentation are highly motivated participants and continuous presence of trained occupational hygiene professionals during, both planning of the study but also to inform, instruct, and be available for questions during the measurements. In conclusion, the self-monitored protocol used in this study amongst chimney sweeps is a valuable and valid method which can be used to collect larger numbers of samples. This is especially valuable for occupations where the workers are working independently, and where the exposure is difficult to monitor with traditional occupation hygiene methods.